HUBUNGAN ANTARA KEPATUHAN MEMBATASI CAIRAN MINUM DAN MOTIVASI PASIEN DENGAN KUALITAS HIDUP PADA PASIEN HEMODIALISA DI RSUD TAMAN HUSADA BONTANG - Khoirul Hadi; Ismansyah Ismansyah; Frana Andrianur (Bajang Institute, 2023)
Chronic kidney failure is a disease that has a tremendous impact on sufferers in the form of the inability of the kidneys to remove metabolic waste so that it will affect their quality of life. It requires the ability to comply with fluid restrictions and a strong motivation from suffering so that the quality of life will improve. Method: This research design is descriptive analytic with a cross sectional approach. With a total sample of 40 patients who are undergoing hemodialysis 2 times a week. Sampling technique with total samplimg that meets inclusive criteria. The study instrument used fluid restriction adherence questionnaires, motivation questionnaires and quality of life questionnaires for kidney failure patients. Then the data were analyzed with univariate and bivariate techniques with the Pearson Chi Square test. Results: The respondents of this study were mostly elderly (46-55 years) namely 15 respondents (37.55), dominated by male respondents as many as 26 respondents (65%), Most of them had undergone hemodialysis for a long period of 2-3 years, Most were quite obedient and obedient in fluid restrictions, had good enough motivation and had the same amount between good quality of life and poor quality of life. The results of the study with Chi Square Test Analysis showed p = 0.002 < α = 0.05 which means there is a relationship between fluid limiting compliance with quality of life and p = 0.001 < α = 0.05 which means there is a relationship between motivation and quality of life. Conclusion: There is a relationship between adherence to limiting fluids, patient motivation and quality of life in hemodialysis patients at Taman Husada Bontang Hospital. If the patient is obedient in limiting fluids and has good motivation then the patient has a good quality of life, and vice versa if the patient is not obedient in limiting fluids then the patient has a low quality of life.